PEMBERDAYAAN PELAKU POSITIVE DEVIANCE DALAM MEMANFAATKAN DAUN KELOR SEBAGAI JAJANAN SEHAT REMAJA PUTRI - Masthalina, Herta (Poltekkes Kemenkes Bengkulu, 2024)
The prevalence of anemia among adolescent girls is 23%, assessed by hemoglobin levels below 12 g/dl. Moringa leaves, containing 28.2 mg of iron, offer a potential solution. This community service activity aimed to increase mothers' knowledge about anemia in adolescent girls and process healthy snacks using moringa leaves. Using a positive deviance approach, the project targeted 20 mothers of adolescent girls, providing education and training on making moringa-based snacks. Three positive deviance practitioners were identified and invited to share their successful experiences in using moringa leaves to combat anemia. They demonstrated four healthy snack recipes: moringa leaf kembang goyang, nuggets, gabus sticks, and rempeyek. Participants then created their own moringa-based snacks at home, including nuggets, sticks, omelettes, and moss pudding. Initially unfamiliar with moringa's benefits and processing methods, participants gained understanding and skills in utilizing moringa leaves as healthy snacks for teenage girls to prevent anemia by the end of the training. This approach effectively combined local wisdom with nutritional education to address adolescent anemia through accessible, home-prepared snacks.